Nurses on the Frontline against the COVID-19 Pandemic: An Integrative Review - Abdullelah Al Thobaity; Farhan Alshammari (Dubai Medical Journal)
COVID-19 has affected the life and health of more than 1 million people across the world. This overwhelms many countries’ healthcare systems, and, of course, affects healthcare providers such as nurses fighting on the frontlines to safeguard the lives of everyone affected. Exploring the issues that nurses face during their battle will help support them and develop protocols and plans to improve their preparedness. Thus, this integrative review will explore the issues facing nurses during their response to the COVID-19 crisis. The major issues facing nurses in this situation are the critical shortage of nurses, beds, and medical supplies, including personal protective equipment and, as reviews indicate, psychological changes and fears of infection among nursing staff. The implications of these findings might help to provide support and identify the needs of nurses in all affected countries to ensure that they can work and respond to this crisis with more confidence. Moreover, this will help enhance preparedness for pandemics and consider issues when drawing up crisis plans. The recommendation is to support the nurses, since they are a critical line of defense. Indeed, more research must be conducted in the field of pandemics regarding nursing.